PENGARUH INKLUSI KEUANGAN DAN LITERASI KEUANGAN TERHADAP KEBERLANSUNGAN USAHA (Studi Pada Pedagang Pasar Pagi Dupa Kencana Tanggkerang Tengah Pekanbaru) - Alfiqri, Ilham; Augustin, Jeneva (Jurnal Daya Saing, 2025)
Abstract: In the current era of globalization, trade is one of the things that a country must do to improve its own economy, both micro and macro trade. The relationship between economic growth is very close to the business world. This study aims to examine the effect of financial inclusion and literacy on business continuity in the morning market traders dupa kencana tanggkerang middle Pekanbaru City. The research method used is quantitative research method and uses secondary data and primary data. The sample in this study was set at 81 out of 415 population measured by utilizing the Slovin formula. The data collection technique used was a questionnaire. The sempel retrieval method uses proportional stratified random sampling. Data analysis was carried out using reflective fist order with the SmartPLS 4.1.0.9 application. The results showed that financial inclusion and financial literacy affect business continuity, with t-statistics values of 3.050 and 10.114, respectively. The results of the study concluded that financial inclusion and financial literacy have a positive and significant effect on business continuity in the morning market traders dupa kencana tanggkerang Tengah Pekanbaru City. Keywords: Financial Inclusion, Financial Literacy, And Business Sustainability